1981
DOI: 10.1021/es00092a008
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)- and cadmium(II)-binding abilities of some New Hampshire freshwaters determined by dialysis titration

Abstract: However, there are two unexpected findings. Firstly, the particle size distributions for the metals are generally coarser than might be anticipated from a foreknowledge of the corresponding particle sizes in ambient air, outside the industrial workplace. It is suggested that this phenomenon is due to the fact that, in the industrial case, small particles originating form combustion and condensation processes may be airborne in sufficiently high number concentrations to favor their coagulation.Secondly, it appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

1982
1982
1991
1991

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 14 publications
2
11
1
Order By: Relevance
“…However, additional measurements at other wavelengths showed that the shapes of the UV-visible spectra of the various soil solutions were quite similar (Table VII). There was a poor correlation between A360 and DOC as has also been found recently for New Hampshire river and lake waters (19).…”
Section: Interstitial Water Chemistry Of Ten Soilssupporting
confidence: 73%
“…However, additional measurements at other wavelengths showed that the shapes of the UV-visible spectra of the various soil solutions were quite similar (Table VII). There was a poor correlation between A360 and DOC as has also been found recently for New Hampshire river and lake waters (19).…”
Section: Interstitial Water Chemistry Of Ten Soilssupporting
confidence: 73%
“…Dialysis bags containing 2 ml of the dialysis medium (0.1 M NaNO 3 , pH 7.0) were suspended into 50 ml of the organic extract solution. The volume of the diffusate (internal dialysis) solution was less than 4% of the reténtate (external dialysis) solution, ensuring a negligible effect of the diffusate solution volume on the chemical equilibrium among complexes present in the reténtate solution (30).…”
Section: Metal Speciation By Equilibrium Dialysis Titrationmentioning
confidence: 99%
“…After the completion of ED experiments with SFA, this approach was extended to seven freshwater samples from southeastern New Hampshire (33). Equilibrium dialysis does not require sample modification such as addition of a supporting electrolyte, so the samples had only to be filtered through a 0.4-^.m polycarbonate membrane before titration with Cu2+ or Cd2+.…”
Section: Amentioning
confidence: 99%